Structural and thermal evolution of the eastern Aar Massif: insights from structural field work and Raman thermometry - Nibourel, Lukas (Swiss J Geosci, 2021)
The thermo-kinematic evolution of the eastern Aar Massif, Swiss Alps, was investigated using peak temperature data estimated from Raman spectroscopy of carbonaceous material and detailed field analyses. New and compiled temperature-time constraints along the deformed and exhumed basement-cover contact allow us to (i) establish the timing of metamorphism and deformation, (ii) track long-term horizontal and vertical orogenic movements and (iii) assess the influence of temperature and structural inheritance on the kinematic evolution. We present a new shear zone map, structural cross sections and a step-wise retrodeformation. From [Formula: see text] onwards, basement-involved deformation started with the formation of relatively discrete NNW-directed thrusts. Peak metamorphic isograds are weakly deformed by these thrusts, suggesting that they initiated before or during the metamorphic peak under ongoing burial in the footwall to the basal Helvetic roof thrust. Subsequent peak- to post-metamorphic deformation was dominated by steep, mostly NNW-vergent reverse faults ([Formula: see text]  22–14 Ma). Field investigations demonstrate that these shear zones were steeper than [Formula: see text] already at inception. This produced the massif-internal structural relief and was associated with large vertical displacements (7 km shortening vs. up to 11 km exhumation). From 14 Ma onwards, the eastern Aar massif exhumed “en bloc” (i.e., without significant differential massif-internal exhumation) in the hanging wall of frontal thrusts, which is consistent with the transition to strike-slip dominated deformation observed within the massif. Our results indicate 13 km shortening and 9 km exhumation between 14 Ma and present. Inherited normal faults were not significantly reactivated. Instead, new thrusts/reverse faults developed in the basement below syn-rift basins, and can be traced into overturned fold limbs in the overlying sediment, producing tight synclines and broad anticlines along the basement-cover contact. The sediments were not detached from their crystalline substratum and formed disharmonic folds. Our results highlight decreasing rheological contrasts between (i) relatively strong basement and (ii) relatively weak cover units and inherited faults at higher temperature conditions. Both the timing of basement-involved deformation and the structural style (shear zone dip) appear to be controlled by evolving temperature conditions.